South Carolina women : their lives and times. - Spruill, Marjorie Julian, 1951-; Littlefield, Valinda W., 1953-; Johnson, Joan Marie (Southern Women : Their Lives and Times., 2012)
The three volumes of South Carolina Women: Their Lives and Times highlight the long and fascinating history of the women of the Palmetto State, women whose stories have oft en been told as well as women whose lives warrant far more attention than they have received. The collection of essays is designed to enrich our understanding of the history of South Carolina and the nation as we examine the lives and times of the dozens of women whose stories appear within. The essays are intended to be of interest to a wide audience as well as useful to scholars at every level. For that reason we have chosen a "life and times" approach, through which the lives of individual women are explored within the context of time and place.